2012
DOI: 10.3390/ijerph9114223
|View full text |Cite
|
Sign up to set email alerts
|

Integral Dose and Radiation-Induced Secondary Malignancies: Comparison between Stereotactic Body Radiation Therapy and Three-Dimensional Conformal Radiotherapy

Abstract: The aim of the present paper is to compare the integral dose received by non-tumor tissue (NTID) in stereotactic body radiation therapy (SBRT) with modified LINAC with that received by three-dimensional conformal radiotherapy (3D-CRT), estimating possible correlations between NTID and radiation-induced secondary malignancy risk. Eight patients with intrathoracic lesions were treated with SBRT, 23 Gy × 1 fraction. All patients were then replanned for 3D-CRT, maintaining the same target coverage and applying a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…For the oesophagus, the mechanistic model was used for risk calculation, using the a value of the stomach ( a ¼ 0.46 Gy À1 ) was adopted [23] and R was given the intermediate value of 0.5, in keeping with the work by D'Arienzo et al [32].…”
Section: Appendix Methods Of Second Malignancy Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the oesophagus, the mechanistic model was used for risk calculation, using the a value of the stomach ( a ¼ 0.46 Gy À1 ) was adopted [23] and R was given the intermediate value of 0.5, in keeping with the work by D'Arienzo et al [32].…”
Section: Appendix Methods Of Second Malignancy Modellingmentioning
confidence: 99%
“…Parameters for thyroid were therefore taken from Cella et al [20] and for the oesophagus the a value used is that for the stomach, with an R of 0.5, in keeping with the work by D'Arienzo et al [32]. All other parameters are from [23].…”
Section: Appendix Methods Of Second Malignancy Modellingmentioning
confidence: 99%
“…Past research comparison of the Mu ratio vs. the integral dose has indicated that Conformal RT had a lower ratio than IMRT and a significantly lower ratio than the ratio of cyberknife (radiosurgery) [14] . The Left and Right Breast Statistical Analysis highlighted the structures of the cavity, PTV, Heart, Breasts, Right Lung, Left Lung, and spinal cord met dose/isodose, dose volume histogram criteria, and protocol 5 point dose limitation constraint of the protocol in all ten cases.…”
Section: Dose Verification Was Accomplished By Comparing the Verificamentioning
confidence: 99%
“…Radiation‐induced secondary malignancy is an issue of growing interest and recent studies have shown that treatment using radiation is associated with increasing in the risk of secondary cancers . Intensity Modulated Radiation Therapy (IMRT) is one of the commonly used methods for treating patients with Nasopharyngeal Carcinoma (NPC) .…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-induced secondary malignancy is an issue of growing interest and recent studies have shown that treatment using radiation is associated with increasing in the risk of secondary cancers. 1 Intensity Modulated Radiation Therapy (IMRT) is one of the commonly used methods for treating patients with Nasopharyngeal Carcinoma (NPC). 2 This is because it is difficult to deliver a satisfactory radiation dose distribution to the NPC target volume by conventional radiotherapy techniques without significantly irradiating the critical tissue structures.…”
Section: Introductionmentioning
confidence: 99%